A critical review of the relationship between post-transplant atherosclerotic events and cytomegalovirus exposure in kidney transplant recipients. Issue 2 (1st February 2020) - Rodríguez-Goncer, Isabel; Fernández-Ruiz, Mario; Aguado, José María
ABSTRACT: Introduction : Cytomegalovirus (CMV) infection after kidney transplantation (KT) has been implicated in the so-called 'indirect effects' attributable to the viral ability to evade host's immunity and trigger sustained inflammation. Whether CMV exposure contributes to the development of post-transplant atherosclerotic events (AEs) remains controversial. Areas covered : This review (based on a PubMed/MEDLINE search from database inception to October 2019) summarizes the proposed mechanisms for the role of CMV in atherogenesis, including accelerated immunosenescence, endothelial injury and inflammatory milieu in the vessel wall. Sero-epidemiological evidence linking CMV exposure and cardiovascular disease in the general population is discussed. Finally, we performed a comprehensive review of observational studies investigating the impact of CMV infection on the occurrence of AE after KT, as well as the potential protective effect of antiviral prophylaxis. Expert opinion : Reviewed studies provide biological plausibility and preliminary clinical evidence pointing to the pathogenic role of CMV in post-transplant atherogenesis. However, no definitive recommendations can be made regarding the use of antiviral prophylaxis to prevent post-transplant AE, since existing evidence is mainly founded on inadequately powered post hoc analysis. Well-designed observational studies should clarify the differential impact of prophylactic or preemptive approaches on the occurrence of CMV-associated post-transplant AE among KT recipients.